Aspalathus linearis as a possible SGLT2 inhibitor : investigating the antihypertensive effects of green rooibos extracts - Willemse, Ilze Verona (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc)--Stellenbosch University, 2023.